PERSEPSI GURU TENTANG GAYA KEPEMIMPINAN KEPALA SEKOLAH DASAR DI GUGUS IV KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Niko Refardian (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about the  ledership styles of headmasters. The population is 79 teachers and the sample is 65 people that taken by Krejcie Table. The instrument of this research is question with Likert scale models  that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the teachers perception about  leadership styles of headmasters at Gugus IV Kecamatan Lembang Jaya Kabupaten Solok stay in good enough category. Key word :leadership styles of headmasters